PENINGKATAN KETERAMPILAN GURU MEMBUAT LKPD BELAJAR DARI RUMAH MELALUI KEGIATAN WORKSHOP DI SDN SUMURPULE SEMESTER 1 TAHUN PELAJARAN 2020/2021 - Sukarno Sukarno (Intersections, 2022)
The aim of research is improve teachers' skills in making BDR LKPD through the implementation of Workshop activities. The research subjects 7 teachers. Data collection techniques with observation and documentation. Data analysis was performed using a comparative descriptive technique. The results of the assessment of the observation of discussion activities showed that in the initial conditions the score showed 47.14, increasing to 69.86 in the first cycle and 89.86 at the end of the second cycle. The explanation regarding the increase in teacher skills in making LKPD in the initial conditions was 50.38 in the first cycle the average value was 69.98 and at the end of the second cycle it increased to 84.85 In terms of improving individual teacher skills in the first cycle there were 4 teachers 57, 14% in the second cycle all teachers stated that their skills had improved with explanations from 4 teachers or 57.14% (VERY GOOD) and 3 teachers or 42.86% (GOOD).